Middle School: Hollywood 101 - James Patterson (London Young Arrow, 2016)
Just when school was at its suckiest, things take a turn for the better when a cool, mysterious new girl shows up. Not only that, she actually wants to be my friend! But, you guessed it, things aren't that simple. And when HOLLYWOOD suddenly rolls into Hills Village, things get very weird very fast. Somehow, unbelievably, I, Rafe Katchadorian, am in the movie business...